Pendampingan Brain Gyam dengan Penerapan Salam Variatif Bangun Bounding pada Siswa SDIT Al-Ghazali Kota Palangka Raya - Dahlia Dahlia; Jainah Jainah; Abdullah Abdullah (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Brain Gym assistance at SDIT AL-Ghazali, Palangka Raya City, Central Kalimantan Province, MBKM students innovate by implementing wake bounding with varied greetings as a form of their dedication to the school. They do this by accompanying Brain Gym in the morning to improve students' fitness and behavior in order to increase their enthusiasm before starting learning activities. The aim of these varied greetings is to make activities at Brain Gym more fun and interesting for students. The ABCD (Asset Based Community Development) method was used in this research. Inculturation, discovery, design, definition, and reflection are the processes carried out. By placing their hand on the picture, they choose a variety of greeting images. The results of accompanying brain exercise activities in the morning by applying varied greetings can create discipline, students' readiness to learn with a happy, enthusiastic mood and become an evaluation for future teachers to create other creative ideas.